Long-term morbidity after multivisceral resection for retroperitoneal sarcoma. Issue 9 (3rd June 2015) - Callegaro, D; Miceli, R; Brunelli, C; Colombo, C; Sanfilippo, R; Radaelli, S; Casali, P G; Caraceni, A; Gronchi, A; Fiore, M
Abstract: Background: More than 60 per cent of patients treated surgically for primary retroperitoneal sarcoma survive for at least 5 years. Extended surgical resection has been proposed for primary disease, but long-term morbidity data are lacking. A cross-sectional study was conducted to assess the long-term morbidity of patients undergoing surgery for retroperitoneal sarcoma. Methods: Patients operated on between January 2002 and December 2011 were eligible for the study. Long-term morbidity was evaluated based on a semistructured clinical interview. Lower limb function was assessed by means of the Lower Extremity Functional Scale (LEFS), a self-report questionnaire with a total score ranging from 0 (low functioning) to 80 (high functioning). Pain was investigated by means of the Brief Pain Inventory – Short Form, with pain intensity scores reported on a scale from 0 (no pain) to 10 (worst pain). Results: Some 243 patients underwent surgery, and 101 of 160 patients who were alive at the time of the investigation responded to the study invitation letter. Finally, 95 patients were enrolled in the study. Sensory impairment of the limbs was reported in 72 patients (76 per cent). The median LEFS score was 60 (i.q.r. 43–73). Mean scores for the pain intensity items varied from 1·23 to 2·68. In multivariable analysis, there was no difference in median levels of creatinine at survey between patients who did or did not undergo nephrectomy (difference between median values 13 (95 per cent c.i. −4 to 30) µmol/l; P = 0·170). Conclusion: Severe chronic pain and lower limb motor impairment after multivisceral resection for retroperitoneal sarcomas are rare. Long-term renal function is not significantly impaired when nephrectomy is performed. Abstract : Severe impairment was uncommon